Mutations in SYNGAP1 in Autosomal Nonsyndromic Mental Retardation - Hamdan, Fadi F. (2009)
Although autosomal forms of nonsyndromic mental retardation account for the majority of cases of mental retardation, the genes that are involved remain largely unknown. We sequenced the autosomal gene SYNGAP1, which encodes a ras GTPase-activating protein that is critical for cognition and synapse function, in 94 patients with nonsyndromic mental retardation. We identified de novo truncating mutations (K138X, R579X, and L813RfsX22) in three of these patients. In contrast, we observed no de novo or truncating mutations in SYNGAP1 in samples from 142 subjects with autism spectrum disorders, 143 subjects with schizophrenia, and 190 control subjects. These results indicate that SYNGAP1 disruption is a cause of autosomal dominant nonsyndromic mental retardation.